A cellphone for all standards. - Bing, B.
A new technology called software-defined radio (SDR) could make it possible to keep the same cellphone when switching from one service provider to another to take advantage of deals and new service options, assuming, of course, that service providers choose to adopt it. Software programmability can tailor a cellphone-or any other kind of radio-so that it operates on whatever radio-interface standard is required. As well as looking at how SDR can be used in mobile phone handsets, the article describes the technology and some of the other areas where it is, or may be, applied
Keywords: Cellphone; Mobile phone handsets; Radio-interface standard; Receivers; Service provider; Software defined radio; Software programmability; Transmitters